1986
DOI: 10.1007/bf02035100
|View full text |Cite
|
Sign up to set email alerts
|

Mesenteric vein thrombosis: Early CT and US diagnosis and conservative management

Abstract: We report a case of isolated superior mesenteric vein thrombosis with acute ischemic bowel disease, diagnosed early by a screening ultrasound scan of the upper abdomen and definitively assessed by computed tomography and angiography. This report stresses the contribution of cross-sectional techniques in the early diagnosis and management of venous occlusive disease of the small bowel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

1990
1990
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 8 publications
0
14
0
1
Order By: Relevance
“…AJA:154, January 1990 Initial case reports [6][7][8] showed the utility of CT in identifying thrombus in mesenteric arteries and veins. Additional studies [1 -4, 9] have reported variable results in CT detection of intravascular gas (9-86%), intramural gas (22-73%), and bowel wall thickening (26-91 %) ( Table 4).…”
Section: Smerud Et Almentioning
confidence: 99%
“…AJA:154, January 1990 Initial case reports [6][7][8] showed the utility of CT in identifying thrombus in mesenteric arteries and veins. Additional studies [1 -4, 9] have reported variable results in CT detection of intravascular gas (9-86%), intramural gas (22-73%), and bowel wall thickening (26-91 %) ( Table 4).…”
Section: Smerud Et Almentioning
confidence: 99%
“…Pain did not develop in this patient until well into his hospital course, and the serial CT scans demonstrated no thickening of the bowel wall. 1 In addition, the larger venous structures were well visualized and normal in appearance. Thus, we can rule out both large-vessel venous disease and arterial disease.…”
Section: Vascular Diseasementioning
confidence: 92%
“…9 Computed tomography is now widely acknowledged as the key to early diagnosis of MVT. 5,8,10 Diagnostic findings on CT include visualization of …”
Section: Discussionmentioning
confidence: 99%
“…Visceral arteriography, although invasive, remains the gold standard. 5,10 In a review of 372 cases of MVT, a survival rate of only 8% was reported without surgical intervention. 4 Survival rates only increased by 12% when patients received heparin in conjunction with surgery versus those who had surgery alone.…”
Section: Mesenteric Venous Thrombectomy Followed By Liver Transplantamentioning
confidence: 99%